Local Welfare Policy Making in European Cities - Kutsar, Dagmar (Springer, 2015)
This book focuses on how EU welfare policies are implemented at the local level in 11 European cities and how local policy making addresses women’s care responsibilities. The book studies the complex combination of and the relationships between local political processes, policies, institutions, structural conditions and outputs, as well as outcomes for the women’s labour market integration. It demonstrates how cultural settings and multi-level governance patterns form the “playground” for local policy makers to formulate their welfare policies concerning service provision. The book further demonstrates how local production systems and the situation of the local labour market influence the prospects that women have in working and caring.